ANTIPLATELET THERAPY IN PATIENTS WITH HIGH RISK OF THROMBOTIC EVENTS: THE PROBLEM OF EFFICIENCY, SAFETY AND COMPLIANCE - S. Yu. Martsevich; N. P. Kutishenko; M. L. Ginzburg; A. M. Malysheva; Yu. N. Polyanskaya (Klinicist)
Evidence based medicine data on ability of antiplatelet, including dual antiplatelet, therapy to improve the life expectancy of patients with high risk of thrombotic complications, especially patients with acute myocardial infarction is presented in brief. The problem of choosing a drug and resistance was overcoming. Modern clinical guidelines on safe antiplatelet therapy are presented.